Pandemic Response and Economic Recovery in India: A Critical Analysis of Policy Measures During COVID-19 - Kumar, Teendra Pavan (Journal of Global Economy, Business and Finance, 2025)
COVID-19 infections have been rising since January 30, 2020, due to community transmission. The Indian government had to choose between citizen and economic health during the pandemic. Many believe in the lives over livelihood debate that the Indian government did too little to protect citizens' health, especially marginalized communities. Many believe that by imposing nation-wide lockdowns and closing many sectors of the Indian economy indefinitely, the Indian government did not prioritize its citizens' economic well-being. This paper aims at critiquing both these views, and relates to the success of the Indian government in overcoming the pandemic and mitigating its adverse impacts. This paper aims at reviewing the key factors which led to the strong revival of the Indian economy. Two-fold contribution of the paper: it begins by explaining the government's policy choices, their risks, and how economic models are used to mitigate them. Second, it separates structural variables (for better growth) and policy responses (for better economic resilience) in the Indian economy.